Meningkatkan Berpikir Kritis dan Pemahaman Mendalam Matematika melalui STEM dan Merdeka Belajar: Suatu Tinjauan Sistematis - Idham Kholid (Yayasan Literasi Sains Indonesia, 2025)
Conventional mathematics education often faces the problem of procedural and abstract learning, which fails to cultivate students' critical thinking and deep conceptual understanding. Coinciding with the implementation of the Merdeka Curriculum, which emphasizes contextual learning and competency development, the Science, Technology, Engineering, and Mathematics (STEM) approach emerges as a potential and synergistic solution. This study aims to investigate the potential of integrating STEM within the Merdeka Belajar framework to enhance deep learning and critical thinking in mathematics through a Systematic Literature Review (SLR). The research method followed the PRISMA protocol, analyzing selected articles from the Scopus, Garuda, and Google Scholar databases published between 2019 and 2024. The synthesis results reveal that STEM learning designs, which position mathematics as a tool for solving authentic problems integrated with the engineering design cycle, effectively create an intrinsic need for students to understand concepts deeply and train their analysis, evaluation, and self-regulation skills. Furthermore, the Merdeka Belajar philosophy provides an ideal structural foundation for STEM implementation through teacher autonomy, a student-centered focus, and authentic assessment. The study concludes that the integration of STEM and the Merdeka Curriculum forms a powerful synergy for transforming mathematics learning. The implication is that teachers need to be empowered to act as collaborative learning designers, while supportive policies such as teacher capacity building and adequate resource allocation are prerequisites for the success of this transformation in the classroom.